FUTURE SPECIALIST’S KULTURAL PREPARATION IN INFORMATION SOCIETY (Journal of Information Technologies in Education (ITE), 2015)
The article is devoted to theoretical and methodical basics of future specialist’s information culture formation as another form of communication and life in a new ontological reality. Theoretical bases of interrelation of culture and education arising from the nature and genesis of culture development as a social and personal phenomenon. Cultural characteristics of modernity are analyzed: a virtual mode of culture existence, the trend of greening culture. The authors examine the impact of personal factors on the process of culture development in the information society, analyze the symbolic nature of the activities in the information society, and focus on the virtualization of life as the culture of the information society. Theoretical investigation of the concept of personality information culture is made, its informative value,structural components and features of the formation. It is proved that in the process of planning the cultural training is important to consider such principles as continuity, sufficiency, consistency and practical application. The methods of students’ stimulation to information activities are disclosed. The main directions of the experimental searches of cultural training organization are determined: improving the content, forms and methods of future primary school teachers’ professional training, the use of innovative pedagogical techniques, computer tools and technologies. The possible results of students’ information activity in University are described.
Keywords: information society; personality information culture; information activities; future specialis